Prognostic impact of elevated baseline CRP levels in primary PCI-treated patients with residual cholesterol risk. (25th November 2020) - Zobenica, V; Milasinovic, D; Jelic, D; Mehmedbegovic, Z; Zaharijev, S; Radomirovic, M; Djurosev, I; Pavlovic, A; Dudic, J; Dedovic, V; Asanin, M; Vukcevic, V; et al.
Abstract: Background: Recent large randomized studies have indicated the potential of anti-inflammatory therapies to reduce adverse cardiovascular events in patients with myocardial infarction, with the most pronounced benefit in patients with baseline elevated C-reactive protein (CRP). Purpose: Our aim was to assess the association of CRP levels with 30-day and 1-year mortality in patients with acute myocardial infarction treated with primary PCI and with residual cholesterol risk. Methods: The study included 1531 patients admitted for primary PCI, with the residual cholesterol risk, i.e. low-density lipoprotein cholesterol (LDL-C) levels of >1.80 mmol/l (70 mg/dl), from a prospectively kept electronic registry of a high-volume tertiary center, for whom in-hospital CRP measurements were available. Elevated CRP was defined as ≥5 mg/l (local laboratory cut off value), measured during index hospitalization. Cox regression models were constructed to assess the impact of elevated CRP on 30-day and 1-year mortality. Results: 72% of the included patients with LDL-C >1.80 mmol/l had elevated in-hospital CRP (n=1107). Compared with patients with CRP levels within reference limit, elevated CRP was associated with older age (62 vs. 60, p<0.001), higher rates of diabetes (25.8% vs. 18.5%, p=0.002), renal failure (6.4% vs. 2.1%, p<0.001) and Killip class >1 at presentation (22.5% vs. 12.3%, p<0.001), as well as lower EF (44% vs. 48%, p<0.001) and lower haemoglobin on admission (13.9 g/dl vs. 14.2 g/dl, p<0.001). Crude mortality rates were increased in patients with CRP ≥5mg/l at both 30 days (6.0% vs. 2.4%, p=0.003) and 1 year (13.2% vs. 6.3%, p<0.001) (Figure). After adjusting for the observed baseline differences, CRP ≥5mg/l remained an independent predictor of mortality at 1 year (HR 1.691, 95% CI: 1.050–2.724, p=0.03), but not at 30 days (HR 1.690, 95% CI: 0.859–3.324, p=0.13). Conclusion: In primary PCI-treated patients with residual cholesterol risk, elevated in-hospital CRP was independently associated with 1-year mortality. Our findings may thus suggest a potential window of opportunity, for anti-inflammatory therapies to improve outcomes beyond the acute phase. Funding Acknowledgement: Type of funding source: None